THE EFFECT OF LACK OF VOCABULARY MASTERY ON THE ABILITY TO UNDERSTAND QUESTIONS IN THIRD GRADE STUDENTS AT PELANGI ELEMENTARY SCHOOL - Eva Betty Simanjuntak; Dea Yuanita Nasution; Siti Masitoh Hasibuan; Pelangi Zingga Sinaga; Yunita Eryana Br Sirait; Andreas William Laia (PT. Intelek Cendikiawan Nusantara, 2025)
This study aims to evaluate the level of vocabulary mastery in relation to English comprehension skills among third-grade students at Pelangi Elementary School. Vocabulary is an important foundation in the learning process, especially in understanding instructions and questions contained in lesson questions. A lack of vocabulary mastery can be a significant obstacle for students in interpreting the meaning of questions, thereby affecting their learning outcomes. This study uses a descriptive qualitative method through observation, interviews, and documentation. Data were collected from English teachers and students through various techniques, as well as vocabulary tests to measure students comprehension levels.